2015
DOI: 10.1016/j.coldregions.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Stress measurements from common snow slope stability tests

Abstract: In the majority of fatal snow avalanches, skiers and snowmobilers trigger the avalanche by applying load to the snow cover. The snow cover is often tested to learn information about its stability on surrounding slopes. This testing is normally performed by digging down into the snow cover, isolating a column of snow, dynamically loading the top of the column and observing fractures that occur in the column due to the loading. Understanding how stress from dynamic surface loads and from loading in common stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Motivated by avalanche release, a variety of field-based studies have measured the snow's response to dynamic loads in naturally occurring mountain snowpacks. In these experiments, the most controlled and repeatable loading methods have involved dropping a known weight from a known height as performed with the Rammrutsch (Schweizer and others, 1995) and a drop hammer (Thumlert and Jamieson, 2015). Additionally, stability test loading schemes have been implemented to impact the snow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by avalanche release, a variety of field-based studies have measured the snow's response to dynamic loads in naturally occurring mountain snowpacks. In these experiments, the most controlled and repeatable loading methods have involved dropping a known weight from a known height as performed with the Rammrutsch (Schweizer and others, 1995) and a drop hammer (Thumlert and Jamieson, 2015). Additionally, stability test loading schemes have been implemented to impact the snow.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, stability test loading schemes have been implemented to impact the snow. These include hand taps during compression tests/extended column tests (van Herwijnen and Birkeland, 2014;Thumlert and Jamieson, 2015;Griesser and others, 2023) and Rutschblock loading (Schweizer and others, 1995;Schweizer and Camponovo, 2001). More realistic avalanche triggers and less repeatable loading methods have included skiing with a knee dip, skiing and falling and snowmobiling (Thumlert and others, 2012;Thumlert and Jamieson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Logan (2006) made measurements of hand taps during a conference to learn more about timing, impact force and technique, but the results were never published. Thumlert and Jamieson (2015) impacted the snow with both a drop hammer and hand taps and measured the resulting stress within the snow. Griesser et al (2023) measured the impact force from 62 participants from the European Avalanche Warning Services, as well as a field-based study where they measured stress within the snowpack.…”
mentioning
confidence: 99%
“…There have been limited studies regarding the influence of snowmobile use on snowpack properties (Keddy et al, 1979;Thumlert et al, 2013;Thumlert and Jamieson, 2015). Studies have, however, examined how the snowpack changes due to snow grooming at ski resorts (Fahey et al, 1999;Keller et al, 2004;Spandre et al, 2016a), or to traction and mobility of wheeled vehicles across a snowpack (Abele and Gow, 1975;Shoop et al, 2006;Pytka, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a doubling of fresh snow density and a compression of the natural vegetation below the snow (Keddy et al, 1979). Examining deeper snow cover (> 20 cm deep), Thumlert et al (2013) and Thumlert and Jamieson (2015) examined the distribution of stresses through the snowpack due to type of loading, depth and snowpack stratigraphy (Thumlert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%